REGISTRATION OF INTELLECTUAL PROPERTY RIGHTS TO “KOPI TAMBAH WAKTU” BRAND BASED ON INTELLECTUAL PROPERTY RIGHTS - Evita Intan Ceria; Febri Jaya (Universitas Internasional Batam, 2022)
One of the Intellectual property rights is a trademark. Brands are needed as identification on an item with the aim of making it easier for someone to recognize an item on the brand. A person can easily recognize a product on a brand by name or image. If a mark wants to get legal protection, the trademark owner must submit an application for registration of rights to the mark. The advantage obtained in registering a trademark is that other parties cannot use the mark without permission and cannot imitate the mark. An item that has its own brand has a higher value, where someone can trust the product more. Products that do not have a brand make the value of a product not too high, a person's lack of trust in buying and can result in the product not selling well. The problem that is currently rife is the imitation of brands by other parties which is not allowed so that the owner of the mark registers the “Kopi Add Time” mark to DJKI. The method used is through observation, interviews and literature study through laws and regulations, legal journals, expert opinions. The result is success in assisting the